Abatacept retention and clinical outcomes in Austrian patients with rheumatoid arthritis: real-world data from the 2-year ACTION study - Peichl, Peter; Alten, Rieke; Galeazzi, Mauro; Lorenz, Hanns-Martin; Nüsslein, Hubert; Navarro, Federico; Elbez, Yedid; Chartier, Melanie; Hackl, Roland; Rauch, Christiane; Connolly, Sean E. (Wiener Medizinische Wochenschrift, 2019)
Background AbataCepT In rOutiNe clinical practice (ACTION; NCT02109666) was a 2-year international observational study of patients with moderate to severe rheumatoid arthritis. Methods Baseline characteristics, abatacept retention rates, and clinical outcomes were compared by treatment line in the Austrian cohort of ACTION. Results Of 100 patients enrolled in Austria, 98 (98.0%) were evaluable: 33/98 (33.7%) biologic naive and 65/98 (66.3%) with >= 1 prior biologic failure. At baseline, biologic-naive patients had shorter disease duration and lower concomitant corticosteroid use than biologic-failure patients. Overall crude abatacept retention rate was 60.5% and retention rate was higher in biologic-naive (65.1%) versus biologic-failure (58.0%) patients. Good/moderate EULAR (European League Against Rheumatism) response rates were 85.7% in biologic-naive and 100% in biologic-failure patients. Conclusions In the Austrian cohort of ACTION, overall abatacept retention at 2 years was high, with higher retention rates in patients receiving abatacept as an earlier treatment line. Good/moderate EULAR response rate was higher in biologic-failure than in biologic-naive patients.
CRIS-Team WoS Importer:2019-11-08